Vertebrate-class-specific binding modes of the alphavirus receptor MXRA8 - Zimmerman, Ofer; Zimmerman, Maxwell I.; Raju, Saravanan; Nelson, Christopher A.; Errico, John M.; Madden, Emily A.; Holmes, Autumn C.; Hassan, Ahmed O.; VanBlargan, Laura A.; Kim, Arthur S.; Adams, Lucas J.; Basore, Katherine; et al. (Cell, 2023)
MXRA8 is a receptor for chikungunya (CHIKV) and other arthritogenic alphaviruses with mammalian hosts. However, mammalian MXRA8 does not bind to alphaviruses that infect humans and have avian reservoirs. Here, we show that avian, but not mammalian, MXRA8 can act as a receptor for Sindbis, western equine encephalitis (WEEV), and related alphaviruses with avian reservoirs. Structural analysis of duck MXRA8 complexed with WEEV reveals an inverted binding mode compared with mammalian MXRA8 bound to CHIKV. Whereas both domains of mammalian MXRA8 bind CHIKV E1 and E2, only domain 1 of avian MXRA8 engages WEEV E1, and no appreciable contacts are made with WEEV E2. Using these results, we generated a chimeric avian-mammalian MXRA8 decoy-receptor that neutralizes infection of multiple alphaviruses from distinct antigenic groups in vitro and in vivo. Thus, different alphaviruses can bind MXRA8 encoded by different vertebrate classes with distinct engagement modes, which enables development of broad-spectrum inhibitors. [Display omitted] •Avian but not mammalian MXRA8 is an entry receptor for WEE complex alphaviruses•Mammalian but not avian MXRA8 binds to Semliki Forest complex alphaviruses•Avian and mammalian MXRA8 bind different alphaviruses in flipped orientations•A chimeric duck-mouse MXRA8 inhibits alphaviruses from multiple antigenic groups Avian MXRA8 is an entry receptor for alphaviruses belonging to the Western equine encephalitis complex that have bird reservoirs but not for those in the Semliki Forest complex, which instead utilize mammalian MXRA8. Avian MXRA8 and mammalian MXRA8 engage different alphaviruses using inverted binding modes and distinct regions. A duck domain 1-mouse domain 2 chimeric MXRA8 serves as a decoy-receptor and inhibits infection of multiple alphaviruses from distinct antigenic complexes in vitro and in vivo.